Analysis of ice creams from goat milk kefir and red dragon fruit - Santoso, Aman; Radiati, Lilik Eka; Armaini, Armaini; Mujahidah, Amiroh Nabilah; Sanjaya, Eli Hendrik; Muntholib, Muntholib; Asrori, Muhammad Roy; Damayanthi, Evy (Institute of Advanced Engineering and Science, 2025)
Ice cream from goat milk kefir is lower lactose than cow milk kefir. Combining goat milk kefir with red dragon fruit in ice cream formulations can improve the quality of the product. This study aims to determine the sensory characteristics, total solid, total flavonoid, and antioxidant activity of goat kefir-based ice cream flavored red dragon fruit as quality evaluation. The study used a completely randomized design with 4 treatments and 3 replications. The treatment was the ratio of goat kefir and dragon fruit, including 40:60, 50:50, 60:40, and 70:30 in the ice cream mixture. 30 panelists participated in the organoleptic test. Total solid testing referred to SNI 01-3713-1995. Determination of total flavonoid content was carried out by forming AlCl3 complexes spectrophotometrically and assaying antioxidant activity used 2.2-diphenyl-1-picrylhydrazyl (DPPH) method. The results showed that there was no significant difference in the organoleptic test for taste, color, and texture. The results of the total solids test showed that the higher the addition of goat kefir to ice cream, the lower the total solids produced. While the addition of goat kefir increased the total flavonoids in ice cream. The antioxidant activity with the best formulation of 50:50 was categorized as moderate level, which is 136.59 ppm.